KETERLIBATAN MASYARAKAT DALAM PERKEMBANGAN OBJEK WISATA MAKAM RAJA KECIK KABUPATEN SIAK - Rhecha Valevi; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted in Langkai Village , Siak,Riau- indonesia.this study aims to determine the communitty involvement in the development og the attraction on the tombs of raja kecik Siak Regency.this research uses qualitative method to process the data obtained in the field through interviews, observations and documentations. all the information collected and studied to become a unified whole (Sugono 2000). As for the sample in research 5 key informans.. Based on the results of research that has been donethe communitty involvement in the development og the attraction on the tombs of raja kecik is Mutual Cooperation .and effort to improve the communitty involvement in the development og the attraction on the tombs of raja kecik is increase Promotion, sapta pesona socialization and make travel aware groups . Keywords :Community involvement , Effort and Attractions.